2019
DOI: 10.1038/s41598-019-49612-0
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance hierarchy type and rank contribute to phenotypic variation within cages of laboratory mice

Abstract: A tacit assumption in laboratory animal research is that animals housed within the same cage or pen are phenotypically more similar than animals from different cages or pens, due to their shared housing environment. This assumption drives experimental design, randomization schemes, and statistical analysis plans, while neglecting social context. Here, we examined whether a domain of social context—social dominance—accounted for more phenotypic variation in mice than cage-identity. First, we determined that cag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 52 publications
4
72
0
Order By: Relevance
“…A cumulative DS for the four baseline days of the SB assessment was used as a final measure of social dominance. In line with previous studies (18)(19)(20)(21)(22), we were able to detect a stable hierarchical structure in both sexes (Figure 1a).…”
Section: Male and Female Dominance Hierarchiessupporting
confidence: 92%
See 1 more Smart Citation
“…A cumulative DS for the four baseline days of the SB assessment was used as a final measure of social dominance. In line with previous studies (18)(19)(20)(21)(22), we were able to detect a stable hierarchical structure in both sexes (Figure 1a).…”
Section: Male and Female Dominance Hierarchiessupporting
confidence: 92%
“…These types of relationships have classically been studied in male animals, as female mice have usually appeared more communal and displayed limited aggression (17). Recent work, however, has demonstrated that female laboratory mice also form hierarchies that appear quite similar to those seen in males, accompanied by some of the same dominance-related physiological markers, such as differences in corticosterone levels (18)(19)(20)(21)(22). Thus, we examined social dominance status as a putative mediator of sex differences in the response to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need to expand our knowledge of stress-related factors influencing social behaviours for the purposes of developing appropriate therapeutics. Refinement of animal models that currently assumes that shared housing implies greater phenotypic similarity though recent studies showing social dominance accounted for more variation in mice than cage-identity [47] would be useful to systematically study the behavioural and physiological consequence of social stress. correlates with rankings from three other dominance tests: urine marking assay, UMA (p=0.0509); agonistic behaviour test, ABT (p=0.0229); and the warm spot test, WST (p=0.0090).…”
Section: Discussionmentioning
confidence: 99%
“…Wild and laboratory rodents form complex and dynamic social structures which typically involve the formation of dominance hierarchies (Kondrakiewicz et al, 2019). These have been observed in the lab in group sizes ranging from three to over a dozen individuals (Horii et al, 2017;Varholick et al, 2019;Wang et al, 2014). Hierarchies improve social stability and reduce severe conflicts and aggression (Curley, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These types of relationships have classically been studied in male animals, as female mice have usually appeared more communal and displayed limited aggression ( König and Lindholm, 2012 ). Recent work, however, has demonstrated that female laboratory mice also form hierarchies that appear quite similar to those seen in males, accompanied by some of the same dominance-related physiological markers, such as differences in corticosterone levels ( Schuhr, 1987 ; van den Berg et al, 2015 ; Varholick et al, 2019 ; Varholick et al, 2018 ; Williamson et al, 2019 ). Thus, we examined social dominance status as a putative mediator of sex differences in the response to adverse events.…”
Section: Introductionmentioning
confidence: 99%